Biological Clock and Reproductive Longevity: Molecular Insights into Ovarian Aging and the Role of Physical Activity - Panas, Zuzanna; Izabela Ślinko; Gabriela Kuliś; Jarmoc, Ewa Dryl; Kacper Krawczuk; Jakub Dziemiańczuk; Mateusz Zimowski; Piotr Kadysz; Agata Kolanek; Mateusz Czajkowski (Quality in Sport, 2026)
Introduction. The "biological clock" remains the primary determinant of female reproductive potential, as fertility is strictly limited by a finite pool of oocytes. In modern society, including professional athletes, the trend toward delayed childbearing has increased the clinical relevance of age-related fertility decline. This review explores the molecular foundations of ovarian aging and the impact of lifestyle on reproductive longevity. Materials and Methods. A narrative review was conducted using PubMed and Google Scholar, focusing on clinical guidelines (ASRM, ESHRE) and recent research regarding oocyte depletion, biomarkers (AMH, AFC), and the influence of physical activity and psychosocial stress on fertility outcomes. Literature Review. Reproductive aging is driven by oxidative stress, mitochondrial dysfunction (reduced ATP production), and degradation of cohesin proteins, leading to increased embryonic aneuploidy and miscarriage rates. While AMH and AFC are reliable for assessing follicle quantity, they remain limited in predicting oocyte quality or spontaneous conception. In active populations, extreme physical exertion and psychological pressure can modulate the ovarian microenvironment, potentially affecting reproductive success and long-term quality of life. Summary and Conclusions. Despite advancements in ART, female age remains the most critical predictor of fertility. To optimize reproductive longevity, it is essential to integrate early fertility education and individualized counseling into the routine medical care of active women.